Nota técnica: Method for remote barometers calibration. - Hidalgo, L.; Hidalgo, J. (Rev. Téc. Fac. Ing. Univ. Zulia)
This paper presents a method to calibrate remote barometers through the use of virtual vertical atmospheric soundings (READY, NOAA) and reference barometers located less than 28 km from the remote barometers. The application of the method to the remote barometer GPS2 with the help of the pattern barometer UB2001A situated 5 km from the GPS2 and some READY soundings gives the calibration rule of sum 1.96Ó0.16 hPa to GPS2 outputs to obtain true pressure. The method may be used in nearly any place of the world but with some restrictions.